Halogenated organic contaminants of concern in urban-influenced waters of Lake Ontario, Canada: Passive sampling with targeted and non-targeted screening. (September 2020) - Zhang, Xianming; Robson, Matthew; Jobst, Karl; Pena-Abaurrea, Miren; Muscalu, Alina; Chaudhuri, Sri; Marvin, Chris; Brindle, Ian D.; Reiner, Eric J.; Helm, Paul
Abstract: Passive samplers are useful tools for monitoring hydrophobic, persistent, and potentially bioaccumulative contaminants in the environment. In this study, low density polyethylene passive samplers were deployed in urban-influenced and background nearshore freshwaters of northwestern Lake Ontario and analyzed for a broad range of both legacy halogenated organic contaminants (HOCs) and halogenated flame retardants (HFRs). Non-targeted analysis was conducted for screening additional halogenated substances. For most compounds, concentrations were greatest in the industrialized Hamilton Harbour and more generally at sites that have stronger influences of wastewater effluent discharges and stormwater run-off through rivers and creeks. Polychlorinated biphenyls (PCBs) remain the dominant class of HOCs in water, with dissolved-phase concentrations ranging from 10 to 4100 pg/L (ΣPCBs), followed by polybrominated diphenylethers (ΣPBDEs; 14–960 pg/L) and the organochlorine pesticides (OCPs; 22–290 pg/L). Several non-PBDE brominated flame retardants (nBFRs) and chlorinated Dechlorane-related compounds were detected, with hexabromocyclododecanes (ΣHBCDD; sum of 3 diastereoisomers) the most abundant (1.0–21 pg/L). Non-targeted screening of samples by high resolution mass spectrometry using Kendrick mass defect plots for data analysis indicated that several other halogenated compounds were present in waters at relatively high abundances compared to the flame retardants, based on semi-quantitative estimates. These included methyl-triclosan, four halogenated anisoles (2, 4, 6-tribromoanisole, dimethyl-trichloroanisole, pentachloroanisole, and pentachlorothioanisole), and pentachloro-aniline. Dissolved-phase methyl-triclosan was estimated to contribute up to approximately 40% of the summed target HOC concentrations. Polyethylene passive samplers provided an excellent medium for both non-targeted screening of HOCs not currently included in monitoring programs and tracking brominated and chlorinated chemicals slated for reductions in uses and emissions through international (Stockholm Convention) and binational (Great Lakes) agreements. Graphical abstract: Image 1 Highlights: Passive samplers showed widespread occurrence of several classes of halogenated contaminants. PCBs, OC pesticides and PBDEs were the three dominant compound classes measured. Halogenated anisoles were abundant and found frequently via non-target screening. Methyl-triclosan may contribute up to approximately 40% of the summed target HOCs. Abstract : Passive sampling with targeted and non-targeted screening is demonstrated as a useful tool for measuring halogenated organic contaminants of concern in water.